KAJIAN EKOTEOLOGI KEJADIAN 1:28 SEBAGAI AMANAT BUDAYA DAN HUBUNGANNYA TERHADAP KERUSAKAN ALAM LINGKUNGAN - Harold Pardede (Sekolah Tinggi Teologi Excelsius, 2024)
Abstract: This article is a study of the study of Genesis 1:28 to understand the cultural mandate or mandate that God gave to humans. The study of this verse will be related to its relation to ecology or environmental science. Through the interpretation of this verse, the author will relate it to the current environmental situation which is also more or less influenced by global warming today. This study uses a spiral hermeneutic method (from text to context), namely an exegetical study that reveals the meaning of the original text of the Bible. and implementation of the meaning of the original text today. Text study: The word